A Novel of Ideals and Fuzzy Ideals of Gamma-Semigroups - Anusorn Simuen; Aiyared Iampan; Ronnason Chinram (Journal of Mathematics)
In this paper, we define new types of ideals, fuzzy ideals, almost ideals, and fuzzy almost ideals of Γ-semigroups by using the elements of Γ. We investigate properties of them.